Frankl-Rödl-type theorems for codes and permutations - Keevash, P; Long, E (American Mathematical Society, 2016)
We give a new proof of the Frankl-Rödl theorem on forbidden intersections, via the probabilistic method of dependent random choice. Our method extends to codes with forbidden distances, where over large alphabets our bound is significantly better than that obtained by Frankl and Rödl. We also apply our bound to a question of Ellis on sets of permutations with forbidden distances and to establish a weak form of a conjecture of Alon, Shpilka and Umans on sunflowers.